Prevalence and risk factors of uncontrolled hypertension in the urban population of Kerala - Lalu, Jishnu Sathees; John, Alexander; Paul, Nimitha; Balasubramanian, Arjun (International Journal Of Community Medicine And Public Health, 2021)
Background: Hypertension is leading risk factor for cardiovascular diseases and stroke, and leads to 12.8% of all deaths in the world. Uncontrolled hypertension doubles the risk of cardiovascular disease among the adults with hypertension. Globally 65% of the treated hypertensive have uncontrolled hypertension and in Kerala about three forth of the treated hypertensive have poor blood pressure control. The burden of uncontrolled hypertension is suggestive of preventable deaths and cardiovascular events. Methods: A cross-sectional study was conducted among 1210 residents of Kochi Corporation of Kerala aged 18 years and above during the period of Sept. 2014 to Sept. 2016. Pre-tested, semi-structured questionnaire was used to collect data on socio-demographic factors such as age, sex, occupation, socio-economic status, education and marital status. Behavioural factors such smoking, alcohol intake, physical activity and dietary factors were collected. Data was analysed by using statistical package for social sciences software version 20.0. Results: The prevalence of uncontrolled hypertension was 13.14% among the study population. Majority of the uncontrolled hypertensive were females (67.3%) and belonged to the age group 45 years and above (92.5%). The independent predictive factors of uncontrolled hypertension were additional salt intake (aOR 3.62; 95% CI 1.36-9.66), health education by a doctor (aOR 3.58; 95% CI 1.48-8.64), poor adherence to medication (aOR 4.45; 95% CI 1.23-16.03) and patients having no other co-morbidity (aOR 3.24; 95% CI 1.36-7.72). Conclusions: The burden of uncontrolled hypertension was high in this urban setting. A comprehensive measure involving doctors and healthcare workers have to be adopted to achieve optimum blood pressure among the hypertensive.